Penggunaan Aplikasi Belanja Online, Gaya Hidup Dan Pengaruhnya Terhadap Perilaku Konsumtif Mahasiswa Prodi Ilmu Ekonomi - Adelina Sianturi; Jesaya Kemalementa; Nasrullah Hidayat; Mita Dewi Nasution; Tuti Yani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research examines the influence of using online shopping applications and lifestyle on the consumptive behavior of economics study program students class of 2021, Medan State University. The method used is quantitative with data analysis techniques, namely using multiple linear regression analysis methods, analyzed using statistical tools, namely SPSS version 29. Data was collected through questionnaires distributed to 41 student respondents. The results of the analysis show that partially the use of online shopping applications does not have a significant effect on students' consumptive behavior. However, lifestyle is proven to have a positive and significant influence on student consumption behavior. Simultaneously, the use of online shopping applications and lifestyle influence the consumption behavior of Medan State University students by 32.9%. These findings reveal that the availability of online shopping applications has not been the main factor driving student consumer behavior. However, a consumptive lifestyle plays an important role in shaping students' consumptive behavior. This research suggests the need for education and assistance for students so they can develop a wiser and more rational lifestyle in consuming goods.